1989
DOI: 10.1111/j.1439-0450.1989.tb00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Nachweis des bovinen Herpesvirus Typ 1 (BHV 1) mittels Intrakutantest

Abstract: Studies on an intradermal test for the diagnosis of BHVl infectionAn intradermal test (delayed hypersensitivity test) for the diagnosis of BHVl infection was evaluated in 791 cattle of 16 dairy farms. The skin reactions were compared with the results of serological examinations using a commercial BHVl ELISA kit (Trachitest).As antigen concentrated, purified and inactivated BHVl was used. The skin reaction (increase of the skin fold thickness) was used for the interpretation of test results.The best results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

1990
1990
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In einer ersten Mitteilung (WIZIGMANN et al, 1989) wurde uber Praxiserfahrungen mit einem BHV I-Intrakutantest an BHV 1-unverdachtigen sowie BHV 1-infizierten und teilweise nachfolgend geimpften Rindern berichtet. Aufierdem umfaken die Untersuchungen auch zahlreiche intrakutane Testergebnisse von Jungtieren mit noch vorhandenen maternalen Antikorpern.…”
Section: Introductionunclassified
“…In einer ersten Mitteilung (WIZIGMANN et al, 1989) wurde uber Praxiserfahrungen mit einem BHV I-Intrakutantest an BHV 1-unverdachtigen sowie BHV 1-infizierten und teilweise nachfolgend geimpften Rindern berichtet. Aufierdem umfaken die Untersuchungen auch zahlreiche intrakutane Testergebnisse von Jungtieren mit noch vorhandenen maternalen Antikorpern.…”
Section: Introductionunclassified
“…AGUILAR-SETIBN et al. (1983), STRAUB et al (1990), WIZIGMANN et al (1989) and CORREA-GIR6N et al (1975) proposed values of 1.6, 2.1, 2.1, and about 2-2.5mm respectively. In our study the threshold was selected based on the analysis of the values of sensitivity, specificity and the agreement of ID test results compared to V N 24 ones.…”
Section: Discussionmentioning
confidence: 98%
“…Soon afterwards, DARCEL and DORWARD (1972) demonstrated a skin hypersensitivity reaction following intradermal administration of inactivated BHV-1 antigen in cattle having BHV-1 neutralizing antibodies. Further it was reported that the intradermal (ID) test, in contrast to serological techniques, enabled differentiation between the calves with passive or active humoral immunity (AGUILAR-SETI~~N et al, 1983;WIZIGMANN et al, 1989), and may be useful to detect seronegative, latently infected animals (AGUILAR-SETIBN et al, 1979). These in addition to the high agreement between the results of ID test and those of serological examinations (CORREA-GIR6N et al, 1975;1977;AGUILAR-SETIEN et al, 1983;WIZIG-MANN et al, 1989) indicate the potential for using the test in the diagnosis of BHV-1 infection in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…One of the disadvantages of the skin test is the prevalence among the seropositive cattle, the DTH-individuals (CORREA-GIR6N et al, 1975WIZIGMANN et al, 1989;AGUILAR-SETI~N et al, 1983). Some of such animals did not change their immune status despite the repeated skin testing, while other ones became positive by ID test probably due to natural infection or another unknown factor.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility of detecting cattle infected with bovine herpesvirus type 1 (BHV-1) following intradermal injection of inactivated BHV-1 antigen was first demonstrated by DARCEL and DORWARD (1972). Further studies documented a diagnostic value of the intradermal (ID) testing (a delayed-type hypersensitivity test) of cattle infected with BHV-1 STRAUB et al, 1990;WIZIGMANN et al, 1989). Since this test is based on the intradermal administration of the virus antigen, it is essential from a practical point of view to know the effect it exerts on the immune status especially in animals free from BHV-1 infection.…”
Section: Introductionmentioning
confidence: 99%